Protecting our wildlife for life: a discussion on how we have failed to protect our rhino populations in the past and what our future options really are - Peters, Justine (Institute of Criminology, 2023)
The poaching of the rhino of southern Africa is not a new debate. In fact, it has been a key area of environmental concern for a number of years. Today, it falls under the rubric of ecological criminology which shall be addressed in this dissertation. I intend to deal with the impact poaching and the illegal trade has had on this endangered species and, in addition, to give an overview of the current measures of the criminal justice system in force to combat it. I shall discuss the international perspective and propose some solutions to prevent the further elimination of the species. Approximately 350 million wild animals and plants are traded each year world-wide, estimated to be worth US $20 billion per year. It is argued that up to a quarter of this trade may be illegal .and, thus after drugs and weapons it is the third most significant trade internationally. This illegal activity continues despite the operation of an international convention aimed to prevent it, the Convention on International Trade in · Endangered Species of Wild Fauna and Flora, (CITES). I shall address many of the attributes of CITES, but also consider its numerous flaws which have failed to protect · the rhino adequately.